Statistical Assessment of Results of Innovation Activity of Regions Статистическая оценка результатов инновационной деятельности регионов - Milevskaya Tatyana S (Bìznes Inform, 2013)
The article considers problems of innovation development in regions, which, as a rule, is provided with innovation activity of companies located in a specific territory. Innovation development of regions should be considered from the point of view of the level of innovation development of relevant branches of industry. The article considers Ukrainian regions and 23 indicators of innovation activity. Application of multidimensional scaling allowed placing regions and indicators in the three-dimensional environment for adequate reproduction of observed distances between them. Selection of a method and system of indicators is justified by optimal nature of the criteria that characterise regional differentiation of the level of development of regions. В статье рассмотрены проблемы инновационного развития в регионах, которое, как правило, обеспечивается инновационной активностью предприятий, находящихся на данной территории. Инновационное развитие регионов следует рассматривать в разрезе уровня инновационного развития соответствующих отраслей промышленности. В работе были рассмотрены регионы Украины и 23 показателя инновационной деятельности. Применение многомерного шкалирования позволило расположить регионы и показатели в пространстве трехмерной размерности для адекватного воспроизведения наблюдаемых расстояний между ними. Выбор метода и системы показателей обусловлен оптимальностью критериев, характеризующих региональную дифференциацию уровня развития регионов.